COVID-19 Pandemic: Global Health Crisis, Economic Consequences, and Social Transformation Worldwide - Zakir Hussain; Imtiaz Mahmood Tahir; Shafqat Rasool; Iftikhar Younis Mallhi; Sabira Sultana; Muhammad Mudassar; Rimsha Zainab; Fethi Ahmet Ozdemir; Gawel Solowski; Jawad Zahir; Akif Saeed Ch; Idrees Khan; et al. (Dialogue Social Science Review (DSSR), 2025)
The COVID-19 pandemic changed economies and cultures around the world, in addition to inflicting an unprecedented global health catastrophe. Its horrific toll on human life spurred requests for quick technical advancement, debates regarding public health recommendations, and heightened awareness of the flaws in medical facilities. Increased unemployment, worldwide recessions, supply chain interruptions, and a growing divide between countries and communities were among the economic effects of the epidemic. Socially, it exacerbated mental health conditions, loneliness, and toxic information while speeding up distant employment, online learning, and digitization. The disaster served as a reminder of the value of international collaboration, preparedness, and resilience in the future battle against pandemics. Keywords: COVID-19, Global Health Crisis, Economic Impact, Social Transformation, Pandemic Preparedness